Endogenous Multihoming and Network Effects: PlayStation, Xbox, or Both? - Foros, Øystein; Kind, Hans Jarle; Stähler, Frank (Management Science, 2025)
Competition between firms that sell incompatible varieties of network products can be fierce because it is important for each of them to attract a large number of users. The literature, therefore, predicts that stronger network effects decrease prices and profits. We show that this prediction hinges critically on an implicit or explicit assumption that each consumer buys only one of the varieties available in the market (singlehoming consumers). We show that multihoming (some consumers buying more than one variety) can arise endogenously if the number of exclusive features that each variety offers is sufficiently large. In sharp contrast to the conventional prediction under consumer singlehoming, we further show that both prices and profits can increase with the strength of the network effects if (some) consumers multihome. However, this does not necessarily imply that profits are higher under multihoming than under singlehoming. On the contrary, multihoming can constitute a prisoner’s dilemma for the firms in the sense that they could make higher profits if each consumer bought only one of the varieties. This paper was accepted by Joshua Gans, business strategy. Funding: This work was supported by The Research Council of Norway (Program Kulmedia).